Alopecia areata different view; Heavy metals - Goknur Ozaydin-Yavuz; Ibrahim Halil Yavuz; Halit Demir; Canan Demir; Serap Gunes Bilgili (Wolters Kluwer Medknow Publications, 2019)
Background: Alopecia areata (AA) is a noncicatricial alopecia affecting any hair-bearing area. Although AA is considered to be an autoimmune disease, oxidative stress has been shown to be an important factor in the etiology of AA. Trace elements are highly essential for humans since they form the building blocks of large molecules, function as the cofactors of enzymes, and have some key biological functions. The aim of this study was to investigate serum levels of heavy metals like iron (Fe), zinc (Zn), manganese (Mn), copper (Cu), magnesium (Mg), cobalt (Co), cadmium (Cd), and lead (Pb) in patients with AA. Materials and Methods: The study included a patient group of 30 with AA and a control group of 31 healthy individuals. Serum levels of heavy metals were measured using atomic absorption spectrophotometry. Results: The 30 patients included 17 (56.7%) men and 13 (43.3%) women with a mean age of 33.8 (range, 19-48) years. Serum Zn and Mn levels were significantly lower and serum Cd, Fe, Mg, Pb, Co, and Cu levels were significantly higher in the patient group compared to that of the control group (P < 0.05 for all). Conclusion: The results indicated that low levels of Zn and Mn are associated with AA while other metals were normal. So Zn supplementation may have some beneficial effect in AA while Fe prescription is fruitless.